Hubungan antara Respirasi Tanah dengan Sifat Tanah Dibawah Kondisi Tegakan Vegetasi yang Berbeda di Ungaran, Jawa Tengah - Jaya, Galang Indra; Avianto, Yovi; Handru, Alan; Novyanto, Amir (Program Studi Agroteknologi INSTIPER, 2024)
Soil respiration is an indicator of the level of soil health in both closed systems (forests) and open systems (agriculture). Conversion of land from natural forest to agricultural cultivation needs attention in the field of sustainability, this is done so that the land can continue to be productive. This research aims to obtain information regarding the relationship between respiration and soil properties in land cover of oil palm (Elaeis guineensis), teak (Tectona grandis), and burflower-tree (Neolamarckia cadamba) in INSTIPER's experimental plantation, specifically in SEAT (Stiper Edu Agro Tourism) Ungaran Regency, Central Java. The method used in this research is a modified Verstraete, namely by observing soil respiration directly on the land. Research data shows respiration rates of 100.1, 95.4, and 25.9 mg CO2 m-2 h-1 for oil palm, burflower-tree, and teak respectively. Soil respiration is influenced by land cover in vegetation. Differences in land cover cause differences in soil properties which then influence the rate of soil respiration. The relationship between soil respiration rate and moisture content, pH, and EC is linear positive, while with volume weight it is linear negative.